IDENTIFICATION OF ASCORBIC ACID IN ORANGE AND PAPAYA AS SUPPORTING BODY METABOLISM PROCESSES - bella ramadhani masitta (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Vitamins are organic molecules that are needed by the body for normal metabolism and growth processes. Vitamins are not carbohydrates, proteins or lipids. The body doesn't just synthesize vitamins. Vitamins based on their solubility in water, there are two, namely water-soluble vitamins (Vitamins B and C) and vitamins that are not soluble in water (Vitamins A, D, E and K). Vitamin C is the best antioxidant known to have benefits to boost immunity, vitamin C is usually found in vegetables and fruits. As an essential vitamin, vitamin C has an important function for the health of the body, the body requires 75 mg of vitamin C for women to 90 mg for men for daily needs. This study aims to determine the levels and content of vitamin C in Sunkist oranges and California papayas in increasing body resistance. The method used in this research is an experimental method, namely descriptive qualitative research, with the sampling technique using purposive sampling method. The results showed that the ascorbic acid identification test showed that Sunkist oranges and California papayas were both fruits that contained ascorbic acid or commonly known as Vitamin C.